Chemical Synthesis of Bioactive Proteins. (1st February 2023) - Harel, Omer; Jbara, Muhammad
Abstract: Nature has developed a plethora of protein machinery to operate and maintain nearly every task of cellular life. These processes are tightly regulated via post‐expression modifications—transformations that modulate intracellular protein synthesis, folding, and activation. Methods to prepare homogeneously and precisely modified proteins are essential to probe their function and design new bioactive modalities. Synthetic chemistry has contributed remarkably to protein science by allowing the preparation of novel biomacromolecules that are often challenging or impractical to prepare via common biological means. The ability to chemically build and precisely modify proteins has enabled the production of new molecules with novel physicochemical properties and programmed activity for biomedical research, diagnostic, and therapeutic applications. This minireview summarizes recent developments in chemical protein synthesis to produce bioactive proteins, with emphasis on novel analogs with promising in vitro and in vivo activity. Abstract : Protein chemistry has evolved remarkably in the past decade, which has enabled the effective production of new molecules with novel physicochemical properties for biomedical research, and therapeutic applications. This minireview summarizes recent developments in chemical protein synthesis to produce bioactive proteins, with emphasis on novel analogs with promising in vitro and in vivo activity.